2018
DOI: 10.1101/505974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symptoms of fatigue and depression is reflected in altered default mode network connectivity in multiple sclerosis

Abstract: Background: Fatigue and depression are frequent and often co-occurring symptoms in multiple sclerosis (MS). Resting-state functional magnetic resonance imaging (rs-fMRI) represents a promising tool for disentangling differential associations between depression and fatigue and brain network function and connectivity. In this study we tested for associations between symptoms of fatigue and depression and DMN connectivity in patients with MS. Materials and methods: Seventy-four MS patients were included on averag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
3
9
0
2
Order By: Relevance
“…Reduced RAI among PLWH. The bilaterally reduced RAIs observed among PLWH are similar to those previously observed across substance use and neuropsychiatric disorders (Alexopoulos et al, 2012;Bartova et al, 2015;Bednarski et al, 2011;Bonavita et al, 2017;Chang et al, 2014;Gauffin et al, 2013;Høgestøl et al, 2019;Lee et al, 2017;Liu et al, 2018;Oyegbile et al, 2019;Peterson BS et al, 2009;Schilbach et al, 2016;Sutherland et al, 2012;Verfaillie et al, 2018;Wang et al, 2019;Wang et al, 2013;Whitfield-Gabrieli & Ford, 2012;Wu et al, 2011;Yin et al, 2016;Zhang & Volkow, 2019;Zhou et al, 2016). Nicotine and other drug dependent individuals have displayed reduced RAIs during acute withdrawal (Lerman et al, 2014;.…”
Section: Supplemental Text and Figure S1-s2 For Methodological Detail...supporting
confidence: 77%
See 1 more Smart Citation
“…Reduced RAI among PLWH. The bilaterally reduced RAIs observed among PLWH are similar to those previously observed across substance use and neuropsychiatric disorders (Alexopoulos et al, 2012;Bartova et al, 2015;Bednarski et al, 2011;Bonavita et al, 2017;Chang et al, 2014;Gauffin et al, 2013;Høgestøl et al, 2019;Lee et al, 2017;Liu et al, 2018;Oyegbile et al, 2019;Peterson BS et al, 2009;Schilbach et al, 2016;Sutherland et al, 2012;Verfaillie et al, 2018;Wang et al, 2019;Wang et al, 2013;Whitfield-Gabrieli & Ford, 2012;Wu et al, 2011;Yin et al, 2016;Zhang & Volkow, 2019;Zhou et al, 2016). Nicotine and other drug dependent individuals have displayed reduced RAIs during acute withdrawal (Lerman et al, 2014;.…”
Section: Supplemental Text and Figure S1-s2 For Methodological Detail...supporting
confidence: 77%
“…In line with the triple network model (Menon, 2019;Menon, 2011), accumulating neuroimaging evidence links neuropsychiatric conditions not only with altered network-level rsFC (Alexopoulos et al, 2012;Bartova et al, 2015;Bednarski et al, 2011;Bonavita et al, 2017;Chang et al, 2014;Gauffin et al, 2013;Høgestøl et al, 2019;Lee et al, 2017;Liu et al, 2018;Oyegbile et al, 2019;Peterson BS et al, 2009;Schilbach et al, 2016;Sutherland et al, 2012;Verfaillie et al, 2018;Wang et al, 2019;Wang et al, 2013;Whitfield-Gabrieli & Ford, 2012;Wu et al, 2011;Yin et al, 2016;Zhang & Volkow, 2019;Zhou et al, 2016), but also with altered task-based network activity (Bartova et al, 2015;Bednarski et al, 2011;E.B. Liddle et al, 2011;.…”
Section: Introductionmentioning
confidence: 92%
“… Bisecco et al (2018) concluded that fatigue was mainly driven by connectivity changes in the DMN, after studying resting-state functional connectivity of the DMN and sensorimotor network in relapsing remitting multiple sclerosis patients with and without fatigue using independent component analysis. A study by Hogestol et al (2019) indicated that symptoms of fatigue were reflected in altered DMN connectivity. Higher DMN connectivity was seen in MS patients with fatigue even with low depression scores in patients with MS. Higher connectivity is generally interpreted to represent stronger connection between regions of a network.…”
Section: Discussionmentioning
confidence: 99%
“…In brain tumor patients, this damage could be the result of brain displacement due to a growing tumor. More recently, resting state studies in multiple sclerosis patients suggested a possible involvement of the DMN in fatigue, as fatigue was associated with increased DMN connectivity, ( Bisecco et al, 2018 , Hogestol et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Still, the findings may pave the way for future clinical or experimental studies examining possible causal mechanisms, and subsequent interventions targeting a specific component of the extended cognitive phenotype of PSF. Further, fatigue is a complex and multifactorial syndrome that often co-occur with depression (Høgestøl et al, 2018), which represents a challenge for all research aiming to target unique and specific characteristics of fatigue.…”
Section: Discussionmentioning
confidence: 99%